2023
DOI: 10.1021/acsami.3c12831
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of a Self-Adhesive Conductive Hydrogel with Long-Term Usability

Yang Bai,
Shiqin Yan,
Yinbin Wang
et al.

Abstract: Although conductive hydrogels (CHs) have been investigated as the wearable sensor in recent years, how to prepare the multifunctional CHs with long-term usability is still a big challenge. In this paper, we successfully prepared a kind of conductive and self-adhesive hydrogel with a simple method, and its excellent ductility makes it possible as a flexible strain sensor for intelligent monitoring. The CHs are constructed by poly­(vinyl alcohol) (PVA), polydopamine (PDA), and phytic acid (PA) through the freeze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Table S5 lists the comparison of the hydrogels studied in this work with the studies reported in the last 3 years in terms of tensile properties, adhesion, self-healing properties, sensitivity, etc. Compared with the properties of the other materials listed, the hydrogels studied in this work showed good comprehensive properties. , …”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Table S5 lists the comparison of the hydrogels studied in this work with the studies reported in the last 3 years in terms of tensile properties, adhesion, self-healing properties, sensitivity, etc. Compared with the properties of the other materials listed, the hydrogels studied in this work showed good comprehensive properties. , …”
Section: Resultsmentioning
confidence: 88%
“…This property makes it well suited for creating adhesive hydrogels that mimic mussel adhesion capabilities on nearly any surface. For instance, Bai et al developed a conductive self-adhesive hydrogel using poly­(vinyl alcohol) (PVA), polydopamine (PDA), and phytic acid (PA) via freeze–thaw cycling, with a tensile strain below 450% and a tensile stress under 225 kPa. The adhesive strengths for wood, pig skin, metal, and PP surfaces were 14.9, 13.4, 7.2, and 4.2 kPa, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…10b). 128 Subsequently, liquid conductive phytate was introduced to prepare conductive, water-retaining, and self-adhesive nanocomposite hydrogels by cyclic freeze–thawing, exhibiting enhanced ductility, biocompatibility, and homogeneity. The introduction of phytic acid enhanced the intermolecular forces with the polymer substrate, and the combination of the catechol group on PDA and hydrogen bonding in the system endowed the hydrogel with good adhesion properties, which could be directly and stably adhered to the skin surface.…”
Section: Properties Of Conductive Hydrogelmentioning
confidence: 99%
“…The excellent performance of the hydrogel can detect the movement of the knuckles, wrists, elbows and ankles, as well as the heartbeat, pulse and other small deformation detection. [135][136][137][138][139] To further enhance capabilities in the field of action recognition, ML algorithms can be introduced. For example, Li et al designed a dual-network polyacrylamide/sodium carboxymethyl cellulose/ tannic acid (PAM/CMC/TA) hydrogel with excellent transparency, adhesion, and remodeling properties.…”
Section: Action Recognitionmentioning
confidence: 99%